Cervical Cancer with The Active And Stable PI3K/MTOR/AKT Pathway In Azerbaijan Patients - Konul, S. Mardanova; Sevinj, E. Rahimzade; Jamil, A. Aliyev; Elchin, B. Mansurov; Elnara, E. Aliyeva; Sabina, Q. Mehdizadeh; Leylakhanim, A. Melikova (Journal of Cervical Cancer, 2024)
Among the reproductive cancers cervical cancer has special place, because the second most frequent cause of cancer-related death among women worldwide. The studies suggested that the PI3K/mTOR/AKT signaling pathway is associated with certain reproductive tumors. A lot of research is ongoing for understanding this pathway evidence of its role in promoting tumorigenesis and recent progress in the development of therapeutic agents that targeted PI3K/AKT. In this a single-arm study included 34 Azerbaijan population woman with HPV-negative cervical tumors. The core genes of PAM signaling pathway were analyzed using RT-PCR method. Our preliminary results suggested that tumorgenesis of HPV-negative cervical cancer patients approximately 25% associated with dysregulation of PAM signaling pathway reason which are core genes alteration. The overall survival times in the PAM-active and PAM-stable patients were not significantly varies. However, the main factor for overall survival times were treatment strategy: both PAM-active and PAM-stable patients who received radiation therapy alone had a shorter overall survival than patients who received radiation plus chemotherapy. The patients with alteration of ATK1 and mTOR genes in PAM signaling pathway had poor prognosis then patients with PIK3CA and PTEN mutation
Keywords: Cervical cancer; genetic alteration; PIK3CA/AKT pathway; PAM-active / stabile; over survival; molecular-genetic analysis